2013
DOI: 10.1155/2013/457186
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Operational Cutting Parameters on Nitinol-60 in Wire Electrodischarge Machining

Abstract: Shape memory alloys are a kind of active materials, which have significant characteristics in comparison with other alloys. Since these materials are applicable in different fields such as aerospace, automobile industry, medicine, and dentistry, the effects of wire electrodischarge machining on the properties of these alloys have been studied. In this paper, changes in the shape recovery ability and microhardness of the machined surface of Nitonol-60 shape memory alloy have been studied considering recasting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…MH value is one of the available measures to check the shape memory effect. Lotfi Neyestanak and Daneshmand [32] reported that a larger value of MH shall indicate the continuation of shape memory effect even after machining. In the present case, Equation (11) shows a single objective function, for which optimization was carried out using the HTS algorithm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MH value is one of the available measures to check the shape memory effect. Lotfi Neyestanak and Daneshmand [32] reported that a larger value of MH shall indicate the continuation of shape memory effect even after machining. In the present case, Equation (11) shows a single objective function, for which optimization was carried out using the HTS algorithm.…”
Section: Resultsmentioning
confidence: 99%
“…The prime requirement after machining of SMA is its shape-memory effect. Shape-memory effect has been correlated to MH [32]. The differential scanning calorimetry (DSC) test is one of the techniques to ensure shape memory effect.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al [5] analyzed the effect of cutting parameters such as T on , T off , power, cutting feed rate, wire tension, and water pressure on surface roughness, MRR, and average gap voltage in the WEDM of high hardness tool steel YG 15(WC 85%, Co 15%) for both rough cutting and finish cutting. Akbar and Saeed [6] cut Nitinol-60 shape memory alloy by WEDM using CuZn 37 wire and de-ionized water as the dielectric to study the cut surface for changes in the shape recovery ability and micro hardness considering recasting and formation of re-solidified layer. They carried out SEM and X-ray analysis (EDXA, XRD) of the machined surface.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The NiTi alloy is in martensitic phase at low temperatures and in the austenitic phase at high temperatures [4]. A review of the literature showed that different manufacturing processes are used for the machining of NiTi alloy such as laser processing method [5][6][7][8][9][10][11][12][13][14][15][16], electrical discharge machining (EDM) [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], electrochemical polishing [32] and abrasive water jet processing method (AWJM) [33,34] for shaping NiTi alloy and also conventional machining methods (Turning [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50], milling…”
Section: Introductionmentioning
confidence: 99%